Beam Dynamics Study on High Intensity Cyclotron for Boron Neutron Capture Therapy - JI Luyu, AN Shizhong, GUAN Fengping, WEI Sumin, BIAN Tianjian, XING Jiansheng, ZHENG Xia, XIE Huaidong, WANG Fei, WANG Zhe, HUANG Peng, CHEN Xinyu, LU Jinrong (Yuanzineng kexue jishu)
The China Institute of Atomic Energy (CIAE) is developing an 18 MeV, 1 mA high intensity cyclotron specifically designed for boron neutron capture therapy (BNCT). This therapy relies on precise neutron beams to target cancerous cells, making the performance and accuracy of the accelerator crucial. To thoroughly evaluate the cyclotron’s capability to accelerate high intensity beams, the entire beam transport process from injection to extraction was meticulously segmented into three distinct regions: the central region, the acceleration region, and the extraction region. Each segment was subjected to comprehensive beam dynamics studies to ensure optimal performance. In the acceleration region, a detailed analysis was conducted to assess the magnetic field’s isochronism and its behavior in resonance. This involved both static and dynamic trajectory calculations to ensure that meets isochronism conditions and avoids serious issues caused by resonance crossing, which could adversely affect beam stability and quality. The capacity of the cyclotron to accept and accelerate the beam was thoroughly evaluated by calculating the stability region and performing intricate phase space matching. Multi-particle tracking simulations were employed to study how the beam envelope responds to space charge forces under varying beam intensities. These simulations are crucial for determining the upper limits of beam current that the cyclotron can effectively accelerate. Finite element analysis software was utilized to model the electric field distribution within the central region of the cyclotron. This step is essential for understanding how the complex geometry of the central region affects the beam’s motion and overall performance. By simulating the electric field distribution, the design was refined to enhance beam quality. Tracking of reference particles allowed for an in-depth analysis of key characteristics such as radial centering, axial focusing, and acceleration phase. These parameters are critical for ensuring that the beam remains well-aligned and focused throughout its journey from the central region through to the acceleration region. Phase space matching between the central and acceleration regions was used to assess how effectively the central region can accept and prepare the beam for acceleration. This matching is crucial for ensuring that the beam’s characteristics are properly aligned and optimized for the acceleration region. In the extraction region, multi-particle tracking methods provided a quantitative analysis of the extraction beam parameters. This involved adjusting the stripping point position and tilt angle to control and optimize the parameters of the extracted beam. Such adjustments are vital for achieving the desired beam quality and ensuring that the beam meets the precise requirements for beam transport. The results of these extensive studies demonstrate that the acceleration region of the cyclotron possesses a sufficiently large stability region. The central region has a phase acceptance of 60°, with radial and axial acceptances measured at 1.33 πmm·mrad and 2.01 πmm·mrad, respectively. The extracted beam spot size is determined to be 9.62 mm×7.64 mm. These results indicate that the cyclotron meets the stringent requirements for handling a 1 mA beam, making it well-suited for its intended application of BNCT.